Killer debt: The impact of debt on mortality - Laura M. Argys; Andrew I. Friedson; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2016)
This study analyzes the effect of individual finances (specifically creditworthiness and severely delinquent debt) on mortality risk. A large (approximately 170,000 individuals) subsample of a quarterly panel data set of individual credit reports is utilized in an instrumental variables design. The possibility of the reverse causality of bad health causing debt and death is removed by instrumenting for individual finances post 2011 using the exposure to the housing crisis based on their 2005 residence. Worsening creditworthiness and increases in severely delinquent debt are found to lead to increases in individual mortality risk. This result has implications for the benefit of policies such as the social safety net, which aims to protect individual finances, by adding reduced mortality to the benefit of any intervention.
Keywords: I1; D14; 330; debt; mortality; creditworthiness